TRAINING IN APPROPRIATE TECHNOLOGY THROUGH DATE FLAVOR TOMATO PROCESSING (TORAKUR) IN BUTU VILLAGE, BONE BOLANGO DISTRICT - Bait, Yoyanda; Liputo, Siti Aisa; Engelen, Adnan (Universitas Negeri Gorontalo, 2024)
This community service aims to increase the skills and knowledge of Butu Village residents in processing tomatoes into value-added products, namely date-flavored tomatoes (Torakur). This activity was carried out by a team of lecturers from the Gorontalo State University Food Technology Study Program in Butu Village, Bone Bolango Regency, Gorontalo Province and is expected to provide an alternative source of income for the local community and minimize losses due to unsold tomatoes. This training involved all village residents, especially housewives and youth. The results of this activity show that participants are able to apply appropriate technology in processing tomatoes and produce products that are ready to be marketed.